2022
DOI: 10.5217/ir.2021.00142
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of very early-onset inflammatory bowel disease in Japan: a retrospective single-center study

Abstract: Background/Aims: Very early-onset inflammatory bowel disease (VEO-IBD), defined as IBD diagnosed in patients younger than 6 years, is a challenge for pediatric gastroenterologists. Although there have been reports regarding VEO-IBD in Western countries, those in Asia are still lacking. This study aimed to investigate the clinical features of Japanese VEO-IBD patients.Methods: Patients with VEO-IBD diagnosed between 2006 and 2019 were evaluated retrospectively. The disease phenotypes were classified into ulcera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Another reason is that patients with IBD are lean and have greater nutritional deficits, which may result in less fibrosis. As patients with intestinal BD are older at diagnosis and tend to have fewer nutritional deficits, they may have a higher incidence of NAFLD than patients with IBD [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Another reason is that patients with IBD are lean and have greater nutritional deficits, which may result in less fibrosis. As patients with intestinal BD are older at diagnosis and tend to have fewer nutritional deficits, they may have a higher incidence of NAFLD than patients with IBD [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…This study has some limitations. Firstly, VEO-IBD is a complex and heterogeneous disease, and the diagnosis of VEO-UC may change as the patient ages [25]. Rialon et al reported that 24% of patients originally diagnosed with UC or IBD-unclassi ed were later reclassi ed as having Crohn's disease [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, high-output ileostomy and long duration of CVC placement may pose management challenges.anthropometric measurements in pediatric UC patients; therefore, to our knowledge, this is the rst study to show the effect of surgery on postoperative growth using Z-scores in pediatric UC patients.This study has some limitations. Firstly, VEO-IBD is a complex and heterogeneous disease, and the diagnosis of VEO-UC may change as the patient ages [25]. Rialon et al reported that 24% of patients originally diagnosed with UC or IBD-unclassi ed were later reclassi ed as having Crohn's disease [26].…”
mentioning
confidence: 99%
“…7,16,17 CD diagnosed in pediatric patients has an aggressive disease course and often exhibits poor response to conventional treatments, thus requiring immunosuppressants or biologics immediately after diagnosis. [18][19][20] However, little is known about its effect on the long-term prognosis of intestinal BD.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have consistently reported that age at disease onset is associated with the prognosis for CD 7,15 ; however, the results are inconsistent for ulcerative colitis 7,16,17 . CD diagnosed in pediatric patients has an aggressive disease course and often exhibits poor response to conventional treatments, thus requiring immunosuppressants or biologics immediately after diagnosis 18–20 . However, little is known about its effect on the long‐term prognosis of intestinal BD.…”
Section: Introductionmentioning
confidence: 99%